1998
DOI: 10.1093/jjco/28.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metastasis in Patients with Uterine Cervical Cancer

Abstract: We report on eight patients who developed brain metastases following uterine cervical cancer. The mean interval between diagnosis of the primary cancer and diagnosis of the brain metastasis was 28.4 months (range: 6.1-61.8 months). Nausea and vomiting due to increased intracranial pressure were the most frequent symptoms. Surgical excision of the brain lesions, followed by postoperative radiotherapy, was performed in three patients. The other five patients received only cranial radiotherapy. When the metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1
16

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 6 publications
6
72
1
16
Order By: Relevance
“…Ikeda et al (7) reported that the initial stage was IIB in four of eight patients with brain metastasis from uterine cervical cancer. In a series of twelve cases from Chura et al (3), nine patients were stage IIB or below, while three patients were higher than stage IIB.…”
Section: █ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ikeda et al (7) reported that the initial stage was IIB in four of eight patients with brain metastasis from uterine cervical cancer. In a series of twelve cases from Chura et al (3), nine patients were stage IIB or below, while three patients were higher than stage IIB.…”
Section: █ Discussionmentioning
confidence: 99%
“…However, it is a rare development in uterine cervical cancer, with an incidence rate of only 0.4% to 1.2% (3,4,7,16). Recently, brain metastasis has been seen more frequently.…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В целом, МГМ рака яичников отграничены небольшими сериями и отдельными описаниями случаев, коих в ли-тературе на конец 2011 года насчитывалось не более 600 [15]. Рак шейки матки обычно имеет местное распространение и чаще дает метастазы по лимфатическим путям в забрюшинные лимфа-тические узлы [9,13]. МГМ рака шейки матки настолько редки, что в литературе встречают-ся лишь единичные описания случаев [4,5,13].…”
Section: Discussionunclassified
“…1) (20,21). On the other hand, uterine cervical cancer with brain metastasis is rare with an incidence of 0.44-1.18% (22)(23)(24), and there are no reports of intra-cavernous metastasis. Here, we describe a case presenting with this combination symptoms as an initial manifestation of uterine cervical cancer.…”
Section: Introductionmentioning
confidence: 99%